2019
DOI: 10.2131/fts.6.137
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity evaluation of oil prepared from the internal organs of the Japanese giant scallop (<i>Patinopecten yessoensis</i>)

Abstract: Discarded scallop internal organs, especially the hepatopancreas, are rich in n-3 polyunsaturated fatty acids such as eicosapentaenoic acid and docosahexaenoic acid. However, they have not been utilized because of their contamination with toxic substances, such as cadmium (Cd), and the occurrence of diarrheic shellfish toxins (DST). We have successfully prepared a high-quality scallop oil (SCO) from the internal organs of the Japanese giant scallop (Patinopecten yessoensis), including the hepatopancreas withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In contrast, the internal organs of Uchiura bay scallops included hepatopancreas, gonads, gills, and mantles that were collected between August 2017 and September 2017. SCO-M and SCO-U were prepared according to the method described previously [ 22 ]. Soybean oil was obtained from Merck KGaA (Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the internal organs of Uchiura bay scallops included hepatopancreas, gonads, gills, and mantles that were collected between August 2017 and September 2017. SCO-M and SCO-U were prepared according to the method described previously [ 22 ]. Soybean oil was obtained from Merck KGaA (Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study showed that administration of SCO-M and SCO-U at a dose of 2000 mg/kg body weight (BW)/day, which is the upper limit dose specified by the OECD Guideline for the Testing of Chemicals No. 474 [ 30 ], did not induce clinical signs or BW changes in ICR mice [ 22 ]. Therefore, 5000 mg/kg BW/day was set as the dose of SCO-M and SCO-U for the single oral dose toxicity study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations